HUBUNGAN KONDUSIFITAS LINGKUNGAN BELAJAR DAN MOTIVASI BERPRESTASI DENGAN PRESTASI BELAJAR AKUNTANSI SISWA - Ana Nurjanah; Sigit Santoso; nurhasan hamidi (Universitas Sebelas Maret, 2020)
AbstractThe objectives of this research are to gain empirical proofs about: (1) the correlation between learning environment conducivity and learning achievement in Accounting; (2) the correlation between learning motivation and learning achievement in Accounting; and (3) the correlation of learning environment conducivity and learning motivation to learning achievement in Accounting. This research used the quantitative research method. Its population was 104 students in Grade XI of Financial and Institutional Accounting Expertise Program at State Vocational High School X. Proportionate random sampling was used to determine its samples. They consisted of 83 students. The data of the research were collected through questionnaire and documentation. The data of this research were analyzed with statistical analysis aided with the computer software of SPSS Version 16. The data analysis was done by using Product-Moment Correlations. The result of the research shows that: (1) the learning environment conducivity have any positive correlation and significant with the learning achievement in Accounting of the students as indicated by the r-value = 0.364 and the significance value = 0.001 ; (2) the learning motivation did not have any positive correlation and significance with the learning achievement in Accounting of the students as signified by the r-value = 0.279, and the significance value = 0.11; and (3) the learning environment conducivity and the learning motivation have any positive correlation and significance with the learning achievement in Accounting of the students as shown by the r-value = 0.413, and the significance value = 0.01.Keywords: Learning environment conducivity, learning motivation, learning achievement in Accounting AbstrakTujuan studi ini adalah memperoleh bukti empiris tentang: 1) hubungan kondusifitas lingkungan belajar dengan prestasi belajar akuntansi; 2) hubungan motivasi berprestasi dengan prestasi belajar akuntansi; dan 3) hubungan kondusifitas lingkungan belajar dan motivasi berprestasi secara simultan dengan prestasi belajar akuntasi. Studi ini dilaksanakan dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah seluruh siswa kelas XI Akuntansi Keuangan dan Lembaga (AKL) di SMK X yang berjumlah 104 siswa. Sampel sebanyak 83 siswa diambil dengan teknik proportionate random sampling. Teknik pengumpulan data dilaksanakan melalui angket dan dokumentasi. Data dalam penelitian ini diperlakukan secara statistik dengan bantuan software SPSS versi 16. Hipotesis dalam penelitian ini diuji dengan analisis Korelasi Product Moment. Hasil studi menunjukkan: 1) terdapat hubungan positif dan signifikan antara kondusifitas lingkungan belajar dengan prestasi belajar akuntansi siswa (r = 0,364, sig = 0,001); 2) tidak terdapat hubungan positif dan signifikan antara motivasi berprestasi dengan prestasi belajar akuntansi siswa r = 0,279, sig = 0,11; dan 3) terdapat hubungan positif dan signifikan antara kondusifitas lingkungan belajar dan motivasi berprestasi dengan prestasi belajar akuntansi siswa (r = 0,413, sig = 0,001).Kata kunci: Kondusifitas lingkungan belajar, motivasi berprestasi, prestasi belajar akuntansi